TO STUDY THE DRUG USE PATTERN IN PRIMARY OPEN ANGLE GLAUCOMA IN A TERTIARY CARE TEACHING - C, Deepa latha; Mb, Leela Pratyusha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To study the drug utilization pattern in patients suffering from primary open-angle glaucoma (POAG) in a tertiary care teaching hospital. Methods: It is a prospective study done on 50 patients of POAG (comprising of individuals belonging to any age group). This study was carried for a period of 2-month, and the data included patient’s demographic details and the drugs prescribed. Data were analyzed for drug use pattern. Results: After screening the prescriptions of patients, it was found out that out of total 50 prescriptions, 30 were males, and 20 were females. Out of 50 prescriptions, prostaglandins (58%) were most commonly prescribed. Î²-blockers (16%) were also prescribed. Fixed dose combination constituted 60% of the prescriptions. Instructions about the route, frequency, and duration of treatment were present in all prescriptions. Drugs prescribed by their generic names were 18.75% and about 81.25% of the drugs were prescribed by their brand names. Conclusions: Fixed drug combination of timolol and dorzolamide was the most frequently prescribed combination. Prescribers must be aware of importance of prescribing drugs with generic names. Keywords: Primary open-angle glaucoma, Intraocular pressure, Fixed dose combination.